Cultural Assets a Destination Branding Concept And Environmental Education in Selo Village Boyolali Regency - Dhea Adela; I Nengah Suastika; I Wayan Lasmawan (The Es Economics and Entrepreneurship, 2022)
Place branding is an endeavor to increase public awareness of a destination by promoting or highlighting its advantages and possibilities so that it can develop its own identity. The major goal of this design is to spread awareness of Selo Village among a larger audience so that the community as a whole can benefit from the wealth of local wisdom values that comprise Selo Village's cultural legacy, such as the value of environmental education. This study uses a qualitative approach with an ethnographic research design and Spradley model data analysis with domain, taxonomy, componential, and cultural theme analysis. Detailed interviews, participant observation, and documentation are methods for gathering data. The findings demonstrate that Selo Village contains cultural assets that translate into verbal and visual concepts and environmental education values. The value of local wisdom contained is seen from Ecological Literacy, namely the interaction between humans and their environment must take place in a balanced and proper condition. Then its role as environmental education includes: 1) as knowledge, forming a basic understanding of the environment as a whole, 2) attitude, helping to develop a system of morals and compassionate attitudes as well as participation in environmental conservation, 3) caring, helping to develop care for the environment. life and the problems in it, 4) skills, helping to acquire skills in identifying, investigating, and solving environmental problems.